Impact of dialectical behavior therapy, acceptance in caregiving relationships, and attachment narrative therapy on emotional empathy in premarital couples - Yadollahi Bastani, Sogol; Atashpour, Seyed Hamid; Farhadi, Hadi (Social Determinants of Health, 2025)
Background: Emotional empathy is a critical determinant of marital satisfaction and conflict resolution, necessitating effective premarital education. This study examined the efficacy of premarital programs integrating Dialectical Behavior Therapy (DBT), Acceptance in Caregiving Relationships (ACR), and Attachment Narrative Therapy (ANT) in enhancing emotional empathy among young couples preparing for marriage. Methods: This quasi-experimental study employed a four-group design to evaluate the efficacy of premarital education interventions based on DBT, ACR, and ANT, against a control group. Data were collected via pre-test, post-test, and one-month follow-up. One hundred twenty young adults (30 per group) preparing for marriage were conveniently sampled from Isfahan's psychological centers in 2023 and randomly assigned. The Basic Empathy Scale (BES-A) measured the outcome. Intervention groups completed eight 90-minute sessions. Data were analyzed using SPSS version 26 with descriptive statistics and repeated measures ANOVA. Results: Between-group analyses indicated that all three interventions—DBT, ACR, and ANT—produced substantial increases in emotional empathy scores at post-test relative to the control condition (partial η²=0.67). Gains were sustained at one-month follow-up. No significant inter-intervention differences emerged immediately post-treatment; however, DBT exhibited superior longevity compared to ANT at follow-up. Conclusion: Premarital programmes grounded in DBT, ACR, or ANT significantly bolster emotional empathy in young adults. These evidence-based approaches offer valuable frameworks for counselling, enhancing emotional attunement, conflict management, and relational resilience. While all proved efficacious short- and medium-term, DBT demonstrated greater durability than ANT. Findings support integrating these modalities into premarital education to cultivate enduring, empathetic partnerships.